2005
DOI: 10.1021/ic048286m
|View full text |Cite
|
Sign up to set email alerts
|

Mono-, Di-, and Tricoordinated Phosphorus Attached to a N−N Unit: An Experimental and Theoretical Study

Abstract: N,N',N'-[Tris(trimethylsilyl)]hydrazino-diphenylphosphane, (TMS)2 N-(TMS)N-PPh2 (1), and N,N',N'-[tris(trimethylsilyl)]hydrazino-phenyl(chloro)phosphane, (TMS)2 N-(TMS)N-P(Cl)Ph2 (2), were obtained in the reaction of bis-[lithium-tris(trimethylsilyl)hydrazide] with Ph(n)PCl(3 - n) (n = 1, 2). The structure and bonding of both species are discussed on the basis of experimentally observed (X-ray, Raman, NMR, and MS) and theoretically obtained data (B3LYP/6-31G(d,p), NBO analysis). Oxidation with sulfur and selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 70 publications
3
56
0
3
Order By: Relevance
“…Triazadiphosphole [1] was recently prepared from (Me 3 Si) 2 N À N(SiMe 3 )PCl 2 [2] and GaCl 3 under mild conditions in a formal GaCl 3 -assisted [3+2] cycloaddition. The second example of a binary azaphosphole, the tetrazaphosphole, [3] was formed in the reaction of Me 3 SiN 3 with Mes*N=PCl (Mes* = 2,4,6-tBu 3 C 6 H 2 ), again catalyzed by GaCl 3 .…”
mentioning
confidence: 99%
“…Triazadiphosphole [1] was recently prepared from (Me 3 Si) 2 N À N(SiMe 3 )PCl 2 [2] and GaCl 3 under mild conditions in a formal GaCl 3 -assisted [3+2] cycloaddition. The second example of a binary azaphosphole, the tetrazaphosphole, [3] was formed in the reaction of Me 3 SiN 3 with Mes*N=PCl (Mes* = 2,4,6-tBu 3 C 6 H 2 ), again catalyzed by GaCl 3 .…”
mentioning
confidence: 99%
“…Also, after further stirring of this reaction mixture for 5 h at -100°C no Me 3 SiCl elimination could be observed; only the starting material was isolated after removal of BF 3 [5] Me 3 SiF, and PFCl 2 could be identified amongst the decomposition products. These failures prompted us to utilize the sterically demanding fluorine-containing Lewis acid B(C 6 F 5 ) 3 . Again, no reaction was observed when 1 was added to a solution of B(C 6 F 5 ) 3 in CH 2 Cl 2 at ambient temperature.…”
Section: Resultsmentioning
confidence: 94%
“…Surprisingly, upon cooling of the above reaction mixture down to 5°C, a large amount of beautiful orange crystals of the new species was obtained (isolated yield 29 %). Single-crystal X-ray studies revealed a surprising 2,4-bis(pentafluorophenyl)-1,3-bis[N-trimethylsilyl-N-bis(pentafluorophenyl)boranyl]amino [1,3,2,4]diazadiphosphetidine (3) as the product (Scheme 2, Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations